Barriers and Strategies: Analysis of the Implementation of Independent Learning Independent Campus (MBKM) at PTKI in Aceh - Fadli, M.; Hanum, Lathifah; Amri, Khairul; Rusli, Rusli (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
The objective of this study is to analyze the challenges encountered in the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) policy in Islamic Religious Colleges (PTKI) in Aceh and to propose strategies to address these challenges and enhance the effectiveness of policy implementation. The study focuses specifically on implementing the MBKM policy in PTKI in Aceh, which is noteworthy due to the unique obstacles relating to infrastructure and human resources in this region. The study offers strategic solutions that can be employed to improve the effectiveness of MBKM policy implementation. Furthermore, it provides valuable insights for other universities in Indonesia that may confront similar challenges in implementing the MBKM policy. This study employs a descriptive qualitative approach to investigate PTKI subjects, using interviews, observations, and policy document analysis. The findings reveal that significant obstacles, including a lack of understanding and awareness, limited technological infrastructure, insufficient internet access, and financial constraints impede the implementation of PTKI in Aceh. To overcome these challenges, strategic efforts are needed to raise awareness and educate stakeholders about MBKM, upgrade technology and internet infrastructure, enhance human resource readiness and training, revise internal policies to support the flexibility of MBKM better, streamline bureaucratic processes, and explore additional or alternative sources of funding to support program implementation.